Strategi Penetapan Harga Usaha Kuliner Masa Kini dan Relevansinya dengan Konsep Keadilan Harga dalam Islam - Rosyidatul Munawwaroh; Qory Juan Firdaus (Al-fiqh, 2025)
This study focuses on the analysis of pricing strategies implemented by contemporary culinary entrepreneurs, by taking the business entities of Kue Balok Lumer and Teh Saring franchises (such as Es Teh Solo) as case studies, to then be critically evaluated using the epistemological framework of Sharia Economic Law (Fiqh Muamalah). Through qualitative methods with an in-depth literature study approach (library research) and market phenomenological observations, this study dissects the anatomy of cost structures, cross-promotion schemes, bundling tactics, exponential price markups on online delivery applications, and indications of predatory pricing practices. The results of the study describe that entrepreneurs currently implement pricing strategies based on platform differentiation and market penetration that result in very high profit margins (reaching more than 400% for Teh Saring products) and price disparities between offline and online outlets due to platform commissions of 20-30%. A critical analysis of Islamic jurisprudence (Fiqh Muamalah) concludes that high profit margins do not automatically constitute Ghabn Fahisy (excessive profit-making) as long as they are based on the principles of mutual consent and transparency, considering that contemporary culinary products are considered tertiary needs (Tahsiniyyat) that complement lifestyles. However, price manipulation practices such as predatory pricing (Siyasah al-Ighraq) and double markups without transparency have the potential to violate the principle of Thaman al-Misl (fair pricing), trigger Gharar (unclear information), and undermine the Islamic business ethics of simplicity (Iqtishad).